Tren Urban Farming Selama Pandemi Covid-19 dan Manfaatnya Terhadap Lingkungan dan Gizi Masyarakat - Afrah; Anastasia Rouli Alodia; Angela Olivia Sitompul (STIKes Payung Negeri Pekanbaru, 2021)
Urban farming is a form of commercial or non-commercial activity related to the production, distribution and consumption of food or other agricultural products that takes place in an urban environment. This research is qualitative research with a literature review approach. The purpose of this research is to find out how the trend of urban farming during the Covid-19 pandemic is and its benefits for nutrition and the environment. During the Covid-19 pandemic, the Indonesian government recommended that Indonesians carry out daily activities at home, whether it’s work or school activities. Because people stay at home, the urban farming trend is an option that people are interested in during the Covid-19 pandemic. Urban farming activities bring various benefits to the environment and community nutrition. The application of urban farming can help reduce the temperature in urban areas and reduce the temperature in buildings so that the use of air conditioning can be minimized. Several studies also show that the application of urban farming can reduce air pollution levels. In addition, with the practice of urban farming, the benefits for the nutritional aspect include increasing food security and improving the nutritional status of the community.